Psychometric Properties of Family-Supportive Supervisor Behavior: Lithuanian Version - Vadvilavičius, Tadas; Burčikaitė, Donata (Psichologija, 2023)
Valid and reliable research methods are needed to assess the family-suportive supervisor behavior in Lithuania. A cross-sectional study was conducted to test the psychometric properties of the Lithuanian version of Hammer et al. (2009) family-supportive supervisor behavior scale (internal consistency, discriminant, convergent and structural validity) in employess sample (N = 180). Results revealed that the Lithuanian version of the family-supportive supervisor behavior had high internal consistency. Adequate convergent validity was confirmed by finding statistically significant positive relationships with social support, and discriminant validity was confirmed by finding statistically significant negative relationships with work–family conflict. Finally, structural validity was confirmed by confirmatory factor analysis, which revealed that the four-factor structure of the questionnaire had the best fit. The results of the research show that the Lithuanian version of the scale of family-suportive supervisor behavior is a suitable measurement instrument, but further studies on the evaluation of the scale are still needed.
Keywords: family–supportive supervisor behavior; psychometric properties; scale validity; reliability